Sus scrofa Linnaeus 1758 - Thu, Aye Myat; Lwin, Ye Htet; Quan, Rui-Chang (Zenodo, 2024)
311. Sus scrofa Linnaeus, 1758 Common name: Eurasian Wild Pig, Wild Boar Myanmar name: Distribution: Distributed in all continents except Antarctica, and on many oceanic islands. In Myanmar, widely distributed and recorded in most of the PAs and RF throughout the country. Published as part of Thu, Aye Myat, Lwin, Ye Htet & Quan, Rui-Chang, 2024, Mammals of Myanmar: an annotated checklist, pp. 147-197 in Mammalia (Warsaw, Poland) (Warsaw, Poland) 88 (3) on pages 185-186, DOI:10.1515/mammalia-2023-0098, http://zenodo.org/record/13913939